DEVELOPMENT OF A “GO IN TRAVEL” TOUR PACKAGE BLOG WEBSITE USING VISUAL STUDIO CODE - Febiola Simatupang; Nazwa Zulfa; Rafly Adhitya; Ririn Handayani; Sandy Sanjaya (Sean Institute, 2023)
Applications and websites that are free to access anywhere really help human life, for example they are used to place orders ranging from purchasing goods, delivery and delivery services. It is no exception in the field of tourism to make it easier for a person or group of people to get to tourist destinations more easily by using applications or websites we can get information regarding recommendations for tourist attractions. This website specifically aims to facilitate traveler users to travel to the tourist spots they want to go to. The limitation of this research is the creation of a blog website that provides information about tour packages using a visual code that will display an introduce page, a list of popular destinations and a list of tour and holiday packages.